2005
DOI: 10.2151/jmsj.83a.279
|View full text |Cite
|
Sign up to set email alerts
|

NOTES AND CORRESPONDENCE Spectral Albedo of Desert Surfaces Measured in Western andCentral China

Abstract: Spectral albedo and nadir reflectance of desert surfaces were measured with spectrometer for spectral region from 0.35 to 2.5 mm in western and central China in spring of 2001 and autumn of 2003. Desert surfaces were mainly gobi and/or sand dune around Qira in southern Taklimakan Desert, Aksu in northern Taklimakan Desert, Ejina in Badain Jaran Desert, and in Tengger Desert. The measured spectral albedos are low (0.05-0.11) at ultraviolet wavelengths but it rapidly increases to 0.2-0.3 at the wavelength about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, absorption by non-BC constituents decreases more rapidly with wavelength than does absorption by BC. Accordingly, both dust 45 and algae 39 play no significant role in the absorption at wavelengths longer than 700 nm and concentrations computed by Eq. ( 2 ) exhibit few changes over the range 700–750 nm.…”
Section: Methodsmentioning
confidence: 97%
“…However, absorption by non-BC constituents decreases more rapidly with wavelength than does absorption by BC. Accordingly, both dust 45 and algae 39 play no significant role in the absorption at wavelengths longer than 700 nm and concentrations computed by Eq. ( 2 ) exhibit few changes over the range 700–750 nm.…”
Section: Methodsmentioning
confidence: 97%
“…Each site was visited once during a campaign conducted in late September 2018. Following the methodology used elsewhere [1][2][3][4] , the rotating input optics, fitted with a flat diffuser, was set up at 70 cm above the surface and 1.5 m away from the heavy-duty tripod where the spectroradiometer was installed. Although the field-of-view (FOV) of our input optics is nominally 180º, prior efforts 3 have shown that over 90% of the surface-reflected upwelling irradiance reaching the input optics corresponds to a visual angle of about 72º.…”
Section: Datamentioning
confidence: 99%
“…Although the correlation between MODISderived estimates and ground-based measurements remained relatively high (R= 0.94), RMBE values were slightly larger in the southernmost part of the desert (27-30° S). Both MODIS-derived data and ground-based measurements show that the albedo at some bright spots in the Atacama Desert may be high enough (up to 0.25 in visible range) for considerably boosting the performance of bifacial photovoltaic technologies (6-12%).The surface albedo is defined as the ratio of surface-reflected irradiance to incident irradiance over a given spectral interval [1][2][3][4] . The albedo varies temporally and spatially as a result of natural processes (such as vegetation growth and snowfall) and anthropogenic activities (deforestation/forestation, agriculture, wildfires, etc.).…”
mentioning
confidence: 99%
See 1 more Smart Citation